Harry Potter and the prisoner of Azkaban [videorecording (DVD)] - Cuarón, Alfonso; Radcliffe, Daniel, 1989-; Watson, Emma, 1990-; Grint, Rupert, 1988-; Rowling, J. K. (Warner Home Video, 2004)
Harry, Ron and Hermione, now teenagers, return for their third year at Hogwarts. There they are forced to face escaped prisoner, Sirius Black, who poses a great threat to Harry. In addition to new experiences, Harry must overcome the threats of Dementors, outsmart a werewolf and finally deal with the truth about Sirius and his relationship with his parents. Harry and friends master advanced magic classes, cross time barriers and change the course of more than one life.